The Title: A Tripartite Biomarker Panel of Systemic Inflammation, Immune Activation, and Tubular Injury (IL-6, suPAR, KIM-1) Predicts Mortality and Cardiovascular Outcomes in End-Stage Renal Disease: A Tripartite Biomarker Panel of Systemic Inflammation, Immune Activation, and Tubular Injury - Li, Tong (Journal of Medical Biochemistry, 2026)
Background: The high mortality in end-stage renal disease (ESRD) is driven by a confluence of inflammatory, cardiovascular, and persistent tubulointerstitial injury pathways. We hypothesized that a multi-domain biomarker panel combining Interleukin-6 (IL-6, inflammation), soluble urokinase plasminogen activator receptor (suPAR, immune activation), and Kidney Injury Molecule-1 (KIM-1, tubular injury) would provide superior prognostic value for fatal and non-fatal outcomes. Methods: We performed a prospective cohort study of 538 prevalent hemodialysis patients. Serum IL-6, suPAR, and KIM-1 were measured at baseline. The primary endpoint was a composite of all-cause mortality and major adverse cardiovascular events (MACE). Secondary endpoints were cardiovascular mortality and heart failure hospitalizations. Cox proportional hazards models and C-statistics were used for analysis. Results: Over a median follow-up of 36 months, 192 patients (35.7%) experienced the primary composite endpoint. In fully adjusted models, each biomarker independently predicted the primary endpoint: IL-6 (HR 1.85, 95% CI 1.51-2.26), suPAR (HR 2.15, 95% CI 1.70-2.73), and KIM-1 (HR 1.67, 95% CI 1.35-2.06). A model containing all three biomarkers demonstrated significantly improved discrimination (C-index 0.81) over models with any single biomarker (C-indices 0.71-0.74) or a clinical model alone (C-index 0.67; p<0.001). Patients in the highest risk category (all three biomarkers in top tertiles) had a 6.8-fold increased risk (HR 6.80, 95% CI 3.85-12.02) for the primary endpoint. Conclusion: The combination of IL-6, suPAR, and KIM-1—reflecting systemic inflammation, innate immunity, and residual tubular damage—creates a powerful, integrative prognostic tool that significantly improves risk stratification for mortality and cardiovascular events in ESRD.